Impact of tricuspid regurgitation on survival in patients with heart failure: a large electronic health record patient‐level database analysis. (5th May 2020) - Messika‐Zeitoun, David; Verta, Patrick; Gregson, John; Pocock, Stuart J.; Boero, Isabel; Feldman, Ted E.; Abraham, William T.; Lindenfeld, JoAnn; Bax, Jeroen; Leon, Martin; Enriquez‐Sarano, Maurice
Abstract: Aims: More evidence is needed to quantify the association between tricuspid regurgitation (TR) and mortality in patients with heart failure (HF). Methods and results: Between 2008–2017, using the Optum longitudinal database, a patient‐level database that integrates multiple US‐based electronic health and claim records from several health care providers, we identified 435 679 patients with new HF diagnosis and both an assessment of the left ventricular ejection fraction and at least 1 year of history. TR was graded as mild, moderate or severe and classified as prevalent (at the time of the initial HF diagnosis) or incident (subsequent new cases thereafter). For prevalent TR, the analysis was performed using a Cox proportional hazards model with adjustment for patient covariates. Incident TR was modelled as a time‐updated covariate, as were other non‐fatal events during follow‐up. Prevalence of mild, moderate and severe TR at baseline was 10.1%, 5.1% and 1.4%, respectively. Over a median follow‐up of 1.5 years, 121 273 patients (27.8%) died and prevalent TR was independently associated with survival. Compared to patients with no TR at baseline, the adjusted hazard ratios for mortality were 0.99 [95% confidence interval (CI) 0.97–1.01], 1.17 (95% CI 1.14–1.20) and 1.34 (95% CI 1.28–1.39) for mild, moderate and severe TR, respectively. In the 363 270 patients free from TR at baseline, incident TR (at least mild, at least moderate, or severe) developed during follow‐up in 12.1%, 5.1% and 1.1%, respectively. Adjusted mortality hazard ratios for such new cases were 1.48 (95% CI 1.44–1.52), 1.92 (95% CI 1.86–1.99) and 2.44 (95% CI 2.32–2.57), respectively. Findings were consistent across all patient subgroups based on age, gender, rhythm, associated comorbidities, prior cardiac surgery, B‐type natriuretic peptide/N‐terminal pro‐B‐type natriuretic peptide, and left ventricular ejection fraction. Conclusions: In this large contemporary patient‐level database of almost half‐million US patients with HF, TR was associated with a marked increases in mortality risk overall and in all subgroups. Future randomized controlled trials will evaluate the impact of TR correction on clinical outcomes and the causal relationship between TR and mortality.